Phytochemistry, toxicity, and acceptability of tawa-tawa (Euphorbia hirta) herbal tea preparations - Trivilegio, Kris Dawn Espela (2010.)
Euphorbia hirta (tawa-tawa) is widely used as a cure for asthma, hemorrhagic dengue fever, pulmonary illnesses and many other ailments.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tawa-tawa.; Euphorbia hirta